The Influence of the Impact of Education in View of Economic Development Planning and Investment on the Contribution of Islamic Education Institutions - Fadlan, Achmad; Isma, As’ad; Jamrizal, Jamrizal; Ridwan, Ridwan (International Journal of Education and Teaching Zone, 2023)
Islamic educational institutions have become a forum for developing meaningful educational values at present and in the future, following society and advances in science and technology. Muslim educational institutions engage in various aspects of life, such as economics, investment, and academic planning. To help improve education quality, education managers must continually enrich their knowledge and skills relevant to their work. Education growth will affect the economic development of a nation and vice versa; economic growth will affect education. Investment in education will significantly encourage sustainable economic development, which also requires organized planning to build solid Islamic educational institutions to produce competitive outputs.